Influence of gender and experience on the maximal instep soccer kick - Shan, G. (European Journal of Sport Science, 2009)
Although soccer is a popular sport worldwide, little work has been done to satisfy the increasing demand for quantitative research on female players. As a result, training programmes for female players are often taken directly from their male counterparts, without appropriate adaptations. In this study, I examine the influence of gender and experience on the maximal instep soccer kick among male and female college students, with equal numbers of novice and skilled players. The data collection equipment consisted of a synchronized system with VICON™ 3D motion capture (nine high-speed cameras, 120 Hz) and NORAXON wireless electromyography. Results showed that trained male and female players have different techniques. After a powerful kick, males naturally follow through with a jump to dissipate residual leg momentum, whereas females avoid this airborne phase; instead, they counteract the momentum with upper-body flexions. Skilled male players displayed a more powerful quasi whip-like movement of the kicking leg and more explosive muscle work patterns (higher maximum and faster increase rate of muscle tension) than skilled females. During training, practitioners should pay special attention to repetitive injuries in small muscles like the adductor magnus. The differences observed may be important for the development of training programmes.